PENGEMBANGAN VIDEO ANIMASI FOLKLORE SUMATERA UTARA UNTUK MENINGKATKAN KETERAMPILAN LISTENING DAN PENGUATAN KARAKTER SISWA KELAS III SDN 060879 MEDAN TIMUR - Aprina Siregar; Albert Pauli Sirait; Apiek Gandamana; Tiarnita Maria Sarjani Br Siregar; Imelda Free Unita Manurung (STKIP Subang, 2026)
This study aims to develop an animated video media based on North Sumatra Folklore and to determine its feasibility, practicality, and effectiveness in improving listening skills and strengthening the character of third-grade students at SD Negeri 060879 Medan Timur. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 23 third-grade students at SD Negeri 060879 Medan Timur. Data collection techniques were carried out through interviews, questionnaires, pretest-posttest tests, and observations. The research instruments included expert validation sheets, teacher and student response questionnaires, listening skill tests, and student character observation sheets. The data were analyzed qualitatively and quantitatively through validity, practicality, and effectiveness tests using N-Gain analysis. The results showed that the North Sumatra Folklore-based animated video media was categorized as highly feasible based on material expert validation of 88%, media expert validation of 89.33%, and test instrument validation of 93.84%. The practicality test results obtained percentages of 89.33% from teachers and 89.21% from students, categorized as highly practical. The effectiveness of the media was indicated by an increase in the average pretest score from 48.75 to 85 in the posttest, with an N-Gain score of 0.71, categorized as high. Therefore, the North Sumatra Folklore-based animated video media is feasible, practical, and effective for improving listening skills and strengthening students’ character in elementary school English learning.